Pengelolaan Sarana Prasarana Dalam Mendukung Kegiatan Operasional Perusahaan - Defina Ramadhani; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
Management of facilities and infrastructure is one of the factors affecting success in a company. One is to support the company's operational activities. The purpose of this study was to find out the management of infrastructure in one of the companies engaged in food and beverage. The research results show that the company has carried out management by doing the planning, procurement, maintenance, inventory, and removal of infrastructure. However, not all infrastructure is in an optimal state. This can be seen from the manual use of the machine and the leaky air conditioning due to the lack of regular maintenance. This study used qualitative methods using data collection techniques, namely observation, interviews, and prior literature, and using purposive sampling techniques.